Replicating Adenovirus-SIV Immunization of Rhesus Macaques Induces Mucosal Dendritic Cell Activation and Function Leading to Rectal Immune Responses - Ko, Eun-Ju; Helmold Hait, Sabrina; Enyindah-Asonye, Gospel; Rahman, Mohammad Arif; Hoang, Tanya; Robert-Guroff, Marjorie (Frontiers in Immunology, 2019)
Inducing strong mucosal immune responses by vaccination is important for providing protection against simian immunodeficiency virus (SIV). A replicating adenovirus type 5 host range mutant vector (Ad5hr) expressing SIV proteins induced mucosal immune responses in rectal tissue associated with delayed SIV acquisition in female rhesus macaques, but the initial mechanisms leading to the induced immunity have not been elucidated. As dendritic cells (DCs) are known to orchestrate both innate and adaptive effector immune cell responses, we investigated their role here. Rhesus macaques were immunized twice mucosally with a replicating Ad5hr expressing SIV Env, Gag, and Nef (Ad-SIV) or empty Ad5hr vector (Ad-Empty). DC subsets and their activation were examined in rectal tissue, blood, and LNs at 3 timepoints after each immunization. Plasmacytoid DCs, myeloid DCs, and Langerhans cells were significantly increased in the rectal mucosa, but only myeloid DCs were significantly increased in blood post-immunizations. All rectal DC subsets showed increased frequencies of cells expressing activation markers and cytokines post-immunization, blood DCs showed mixed results, and LN DCs showed few changes. Rectal DCs responded strongly to the vector rather than expressed SIV antigens, but rectal DC frequencies positively correlated with induced rectal antigen-specific memory T and B cells. These correlations were confirmed by in vitro co-cultures showing that rectal Ad-SIV DCs induced proliferation and antigen-specific cytokine production by autologous naïve T cells. Our results highlight the rapid response of DCs to Ad immunization and their role in mucosal immune activation and identify initial cellular mechanisms of the replicating Ad-SIV vaccine in the rhesus macaque model.